Epidemiology and clinical outcomes of clinically suspected multiple endocrine neoplasia type 1 in South Korea: a nationwide cohort study - Kim, Kyoung Jin; Yu, Min Heui; Hwang, Yoon-a; Moon, Shinje; Hong, Namki; Rhee, Yumie (Frontiers in Endocrinology, 2025)
BackgroundMultiple endocrine neoplasia type 1 (MEN1) is a rare hereditary disorder characterized by multiorgan endocrine tumors, primarily affecting the parathyroid glands, pituitary, and pancreas. Despite its clinical significance, the epidemiology and outcomes of clinically suspected MEN1 in Asian populations remain limited. This study aimed to investigate the prevalence, comorbidities, and mortality risk associated with clinically suspected MEN1 in South Korea.MethodsWe conducted a retrospective cohort study using the Korean National Health Insurance Service database (2003–2020), identifying clinically suspected MEN1 cases via two operational definitions: (1) ICD-10 MEN1 code (D44.8) with medical service records and (2) diagnoses or interventions for at least two MEN1-associated conditions (primary hyperparathyroidism, pituitary adenoma, or duodenopancreatic neuroendocrine tumors). Cases (n = 412) were matched 1:10 with controls (n = 4,120) by age, sex, and index year. Clinical characteristics, comorbidities, and mortality were analyzed using Kaplan–Meier survival analysis and multivariable Cox regression.ResultsThe incidence of clinically suspected MEN1 peaked in individuals aged 40–49 years, with a higher prevalence in females (64.6%). Parathyroid involvement was the most common manifestation (58.6%), followed by pituitary (22.3%) and duodenopancreatic tumors (19.9%). Comorbidities, including diabetes mellitus (22.6%), hypertension (38.1%), and dyslipidemia (20.6%), were significantly more prevalent in MEN1 patients than controls. Mortality was elevated among MEN1 patients (HR 3.69; 95% confidence intervals (CI) 2.56–5.31), particularly those with multiorgan involvement, although hazard ratios varied by organ combination and had wide, overlapping CIs. The mean age at death was significantly younger in MEN1 patients (60.1 years) than in controls (68.0 years).ConclusionsThis nationwide cohort study of clinically suspected MEN1 in South Korea reveals a substantial clinical burden, particularly among patients with multiorgan involvement. Enhanced clinical surveillance and early interventions are essential to improve outcomes for MEN1 patients. Future research integrating genetic testing and clinical data is needed to further guide management strategies.